Translating performative mediated art into virtual reality: A case study. Issue 1 (1st June 2021) - Sansom, Matthew; See, Zi Siang
Park benches are distinctive public spaces that invite a temporary pause for thought and time out from everyday activities and worldly preoccupations. Park Bench Sojourn is a multimodal arts project that explores the uniqueness and universality of these spaces and the kinds of experiences they foster. It asks what it means to be human; surrounded, as we are, by computer technologies and digital media, living lives that are perpetually 'connected' and dispersed through the cloud. It reflects on how our technologically determined lives and lifestyles conspire against us to find opportunities to stop, reflect and be witnesses to lived experience. It is a conceptually playful creative work that shares concerns for health and well-being arising from the contemporary mindfulness movement and the traditional practices and worldviews upon which mindfulness draws. The project is based around a range of experiential sojourns, which require participants to find a bench to sit on and then take a sojourn, or a number of sojourns from the project's website, which may include audio, video, spoken word, or just listening. Other iterations of the project have included a multimedia gallery installation juxtaposing content from a variety of sojourns. Regardless of the format, context or specific content, the project explores ways in which we 'perform' ourselves and mediate experience via digital technologies. In this article, we describe the process of translating this mediated and performative artwork into a VR prototype and directions for future work.